Al-Anashir al-Sab’ah li al-Kafa’ah al-Tarbawiyyah ladai Mu’allim al-Lughah al-Arabiyyah bi al-Madrasah al-Aliyah Al Azhar ‘inda Jaihah Covid 19: Kaifa Tahaqqaqat? / The Seven Elements of Pedagogical Competence among Arabic Language Teachers at MA Al-Azhar: How was it achieved? - Faris Maturedy; Dewi Masruroh (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2023)
Abstract: This study aims to describe the pedagogical competence of Arabic teachers at MA Al Azhar. Researchers use a qualitative approach with a case study model. To obtain the data, the researchers conducted interviews with participants consisting of 3 Arabic teachers at the school. After the data was collected, researchers analyzed the data with the Miles & Huberman model which consisted of 3 stages. That is, data exposure, data reduction and ending with drawing conclusions. The results showed that there are 7 components in pedagogic competence that can be applied by MA Al Azhar Arabic teachers. Namely, (1) Understanding of learning theory (2) Understanding student characteristics (3) Learning design (4) Carrying out learning well (5) Able to use technology-based learning media (6) Ability to carry out evaluations (7) Directing students according to their interests. However, in the element of learning implementation, Arabic teachers need time to adjust to distance learning. Based on the results mentioned, the researchers recommend simulating learning adjustment in times of emergency for Arabic teachers. Therefore, research after this can focus on teacher adjustment in the midst of remote learning during the covid emergency in terms of personality competence and professional competence.المستخلص: هدفت هذه الدراسة إلى وصف الكفاءة التربوية لمعلمي اللغة العربية في المدرسة العالية الأزهر. استخدم الباحثون منهجا كيفيا مع نموذج دراسة حالة. للحصول على البيانات، أجروا المقابلة مع 3 مدرسي اللغة العربية. وتم تحليل البيانات بنموذج Miles and Huberman حيث يتكون من 3 مراحل من عرض للبيانات وتخفيضها والاستنتاج منها. وتوصل الباحثون إلى أن تتوفر 7 عناصر الكفاءة التربوية. وهي (1) فهم نظرية التعلم (2) فهم خصائص الطالب (3) تصميم عملية التعليم (4) تنفيذ عملية التعلم جيدا (5) القدرة على استخدام الوسائل القائمة على التكنولوجيا (6) القدرة على إجراء التقويم (7) توجيه الطلاب وفق ميولهم. في نهاية المطاف علم أن المدرسين يحتاجون إلى مدة يتكيفون فيها مع الظروف والأوضاع عند التعليم عن بعد. بناء على النتائج المذكورة، يوصي الباحثون بمحاكاة تعديل التعلم في الأحوال الطارئة لمعلمي اللغة العربية. لذلك، يتسنى للباحثين فيما بعد التركيز على تعايش مدرسي اللغة العربية أثناء التعليم عن بعد عند الوباء كوفيد 19 من حيث الكفاءة الشخصية والمهنية.